2022
DOI: 10.1017/jfm.2022.395
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the competitive role of global modes in the pattern formation of rotating sphere flows

Abstract: The wake flow past a streamwise rotating sphere is a canonical model of numerous applications, such as particle-driven flows, sport aerodynamics and freely rising or falling bodies, where the changes in particles’ paths are related to the destabilization of complex flow regimes and associated force distributions. Herein, we examine the spatio-temporal pattern formation, previously investigated by Lorite-Díez & Jiménez-González (J. Fluid Mech., vol. 896, 2020, A18) and Pier (J. Fluids Struct., vol. 41, 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 76 publications
4
27
1
Order By: Relevance
“…Similar observations were drawn in the case of the wake behind rotating spheres (Sierra-Ausín et al. 2022), where the core of the instability was also found near the downstream part of the recirculating flow region. Therein, it was concluded that the instability is supported by the recirculating flow region.…”
Section: Linear Stability Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…Similar observations were drawn in the case of the wake behind rotating spheres (Sierra-Ausín et al. 2022), where the core of the instability was also found near the downstream part of the recirculating flow region. Therein, it was concluded that the instability is supported by the recirculating flow region.…”
Section: Linear Stability Analysissupporting
confidence: 85%
“…Other configurations where the primary or secondary instability involves modes with azimuthal component are swirling jets (Meliga, Gallaire & Chomaz 2012) and the wake flow past a rotating sphere (Sierra-Ausín et al. 2022). The unsteady modes and display a similar structure to the unsteady modes discussed in § 4.1.…”
Section: Linear Stability Analysismentioning
confidence: 99%
“…Bi-stability has also been observed in the case of a streamwise rotating sphere, for certain Reynolds number and rotation rates (Lorite-Díez & Jiménez-Gonzáles 2020; Sierra-Ausín et al. 2022). Lorite-Díez & Jiménez-Gonzáles (2020) found a switch between a quasi-periodic low-drag state and a more irregular high-drag state.…”
Section: Discussionmentioning
confidence: 87%
“…When two or more modes present similar thresholds, the dynamics results from a competition of the different modes (Fabre, Auguste & Magnaudet 2008), which cannot be unveiled only through linear stability analysis. In this case, weakly nonlinear analyses can shed light on the emerging trajectories or wake patterns, as performed by Meliga, Chomaz & Sipp (2009a), Citro et al (2016) and Sierra-Ausín et al (2022) for the wake of fixed and rotating spheres.…”
Section: Introductionmentioning
confidence: 99%